Penggunaan Lumbar Pillow Support pada Pasien Tirah Baring - Meisa Ndari, Arni Budi; Yona, Sri; Nurachmah, Elly; Maria, Riri (Journal of Telenursing (JOTING), 2024)
This study aims to explain the use of lumbar pillows in bed rest patients in a supine sleeping position. The method used is a scoping review by searching for articles using keywords in the Scopus, Science Direct, PubMed, EBSCOhost, and ProQuest databases based on inclusion and exclusion criteria. The research results showed that there were 3 articles consisting of 2 studies conducted on total bed rest patients and a study on healthy respondents. Two studies used a combination therapy of a support pillow with existing therapies. Two studies showed that support pillows help distribute pressure in the pelvic, lumbar and thoracic areas and support the lumbar arch which can reduce pain levels and increase the comfort of respondents. The conclusion from this study is that the lumbar pillow can be applied to patients on bed rest and provides effective results when combined with physical therapy, conservative therapy, and modification of sleeping position. Keywords: Lumbar pillow, Pillow support, Comfort, Pain, Bedrest,